Mechanical Properties of Si(1−x)–C(x): Strength and Stiffness of Materials Using LAMMPS Molecular Dynamics Simulation - Petilla, Clint Edrick (Archīum Ateneo, 2024)
This study investigated the mechanical properties (elastic modulus, tensile strength, yield strength, and toughness) of different percent C of silicon carbide (SiC) using molecular dynamics simulations via the large-scale atomic/molecular massively parallel simulator (LAMMPS) with the uniaxial tensile test at four strain rates: 0.1, 0.5, 1.0, and 5.0 m s−1, using the Tersoff potential. The simulation uses 20 × 20 × 20 atoms (108.6 Å × 108.6 Å × 108.6 Å) of the diamond cubic structure of Si, then carbon atoms were placed randomly at 5% intervals from 0–50 percent C. Results show improved mechanical properties when increasing percent C until peaking at 25%, before decreasing. This is caused by the shortest bond length at 25 percent C from the increase of Si=C using the radial distribution function analysis. Increasing the strain rate generally improves the mechanical properties of the material. The deformation mechanism shows that increasing (decreasing) strain rate generally results in multiple (lesser) failure points with a ductile (brittle) fracture mode.